Mathematical modelling of the digital tendon pulleys - Tan, Adin Ming (2010)
A mathematical model of the A2 pulley system will enable us to have a better understanding of the mechanics of the pulley-tendon system. The A2 pulley was modelled based on paralel pulley fibres attached to a phalanx with a tendon passing them. Mechanical properties of the pulleys such as stiffness, strength and friction were included in the model. A convergence test was done to ensure the accuracy of the test. The model managed to show the degree of flexion of the fingers affect the force distribution of the pulleys. High loads on flexed finger may lead to pulley ruptures. Further studies on the rupture mechanism showed that pullley ruptures are self propagating when a constant is applied and the rate of rupture increases as less intact fibres are present to support the load. In addition to human application, the model was applied to animals as well, and it proved the advantages of a curved phalanx as compared to a straight one. This is important in deciding the aboreality and terrestiality of primates and hominids. Further application includes explaining the tendon locking mechanism in bats, birds, and some climbing rodents. The relationship between friction coefficient of the pulley-tendon interface and the residual force at the proximal tendon was developed for the tendon locking mechanism.